Local Development and Freedom. Evidences From Italian Provinces - Capriati Michele (European Regional Science Association (ERSA), 2006)
The work is based on the belief that the suggestions of important economists and international organizations on the aims of human development are particularly important to define the most efficient policies for local systems. These contributions emphasize the role of instrumental liberties in the determination of a wider access for the individuals to the occasions of self realization offered by the context. On these basis has been realized an empirical analysis and has been proposed a synthetic index of effective freedom in the Italian provinces. It has shown the existence of interesting territorial differences, which is not always possible to bring back to the north-center/ south dichotomy. The end of the essay is focused on some first indications of policies for local development.
Keywords: 330